2020
DOI: 10.1002/agj2.20088
|View full text |Cite
|
Sign up to set email alerts
|

Direct assimilation of measured soil water content in Root Zone Water Quality Model calibration for deficit‐irrigated maize

Abstract: Correct soil water simulation is critical for water balance and plant growth in agricultural systems. Crop production simulation errors have often been attributed to a lack of accuracy in soil water content (SWC) estimates. However, only a few studies have quantified the effects of SWC estimate errors on crop production and evapotranspiration (ET), especially under different irrigation treatments. The objective of this study was to investigate the impacts of direct assimilation of measured SWC during model cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In the current case, RZWQM2-S daily T was generally in good agreement with T M with the Flow32-1K equipment. Similarly, Qi et al [34] and Sima et al [35] demonstrated that the RZWQM2 S the crop ET well under full and deficit irrigation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the current case, RZWQM2-S daily T was generally in good agreement with T M with the Flow32-1K equipment. Similarly, Qi et al [34] and Sima et al [35] demonstrated that the RZWQM2 S the crop ET well under full and deficit irrigation.…”
Section: Discussionmentioning
confidence: 81%
“…The RZWQM2, a hybrid model between RZWQM and DSSAT4.0, has been applied to optimize field management practices for crop growth under different climate conditions [29][30][31]. This model also performed well in simulating crop growth and soil water content under different deficit irrigation conditions [32][33][34][35]. Li et al [36] and Fang et al [37] reported that the RZWQM2 was appropriate for simulating crop growth and yield under deficit strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, calibrating only plant‐related parameters in crop models does not necessarily improve the simulation of soil water flux‐related key variables. The existence of compensating effect during parameter calibration in crop models (Sima et al., 2020) leading to nonuniqueness, as defined already for hydrological models in the early 1990s (Beven, 1993) is still a challenging aspect in the calibration approach. The problem that models are often right for the wrong reason (Kirchner, 2006), when only a single criterion is considered in model calibration (Houska et al., 2021), is added here as a challenge to calibration.…”
Section: Discussionmentioning
confidence: 99%
“…However, calibrating only plant-related parameters in crop models does not necessarily improve the simulation of soil water flux-related key variables. The existence of compensating effect during parameter calibration in crop models (Sima et al, 2020) leading to nonuniqueness, as defined already for hydrological models in the early 1990s (Beven, 1993) is still a challenging aspect in the calibration approach.…”
Section: Modeling Agroecosystemsmentioning
confidence: 99%
“…The altered weather conditions significantly influence SWC and cropland growth components. Sima et al [27] and Hu et al [2] suggested that higher supplementary water increased the simulation errors for SWC and crop biomass, and the simulation errors were influenced by the background soil water condition. Therefore, it is necessary to monitor and simulate the response of SWC, and crop growth and grain yield to climate change.…”
Section: Introductionmentioning
confidence: 99%